Backbone resonance assignment of the BCL6-BTB/POZ domain - Lin, Li-Ying (Biomol NMR Assign, 2017)
BCL6 is a transcriptional repressor. Two domains of the protein, the N-terminal BTB-POZ domain and the RD2 domain are responsible for recruitment of co-repressor molecules and histone deacetylases. The BTB-POZ domain is found in a large and diverse range of proteins that play important roles in development, homeostasis and neoplasia. Crystal structures of several BTB-POZ domains, including BCL6 have been determined. The BTB-POZ domain of BCL6 not only mediates dimerisation but is also responsible for recruitment of co-repressors such as SMRT, NCOR and BCOR. Interestingly both SMRT and BCOR bind to the same site within the BCL6 BTB-POZ domain despite having very different primary sequences. Since both peptides and small molecules have been shown to bind to the co-repressor binding site it would suggest that the BTB_POZ domain is a suitable target for drug discovery. Here we report near complete backbone (15)N, (13)C and (1)H assignments for the BTB-POZ domain of BCL6 to assist in the analysis of binding modes for small molecules.